Enhancing processed quality of roasted eel with ultrasound treatment: Effect on texture, taste, and flavor. Issue 7 (9th May 2022) - Hao, Gengxin; Lin, Shuting; Jiang, Yafei; Cao, Wenhong; Liu, Ya; Chen, Zhaohua
Abstract: To enhance processed quality, ultrasound treatment was used in eel products processing. This study aimed to investigate the effects of ultrasonic power on the processed quality of roasted eel. Prior to toasting, eel muscle was treated with ultrasonic power from 0 W to 1000 W. Results showed that the highest water content (80.0%) was produced with 600 W ultrasound. Ultrasound above 400 W increases the hardness and chewiness of ( p < .05). The SEM results illustrated the application of ultrasound promoted a more porous and homogeneous network. 600 W ultrasound can increase the umami amino acids, and enhance the content of adenosine monophosphate ( p > .05) and inosine monophosphate ( p < .05). Thiobarbituric acid was increased by ultrasound, especially over 600 W ( p < .05). Polyunsaturated fatty acids changed greatly due to the ultrasound treatment (42.50% 38.91%). Samples treated with 400 600 W had the most abundant volatile organic compounds. In conclusion, ultrasound treatment especially within 600 W enhanced the processed quality of roasted eel. Novelty impact statement: This work further investigates effect of ultrasonic power on processed quality of roasted eel in ultrasonic assisted processing, including the influences on texture, taste and flavor. The application of ultrasound helped to obtain a more porous and homogeneous network. Meanwhile, ultrasound treatment can increase protein degradation and lipid oxidation, and finally promote the formation of umami contents and volatile organic compounds.